Maternal views on facilitators of and barriers to breastfeeding preterm infants - Maria Lorella Gianni; Elena Nicoletta Bezze; Patrizio Sannino; Michela Baro; Paola Roggero; Salvatore Muscolo; Laura Plevani; Fabio Mosca (BMC Pediatrics, 2018)
Abstract Background The supply of breast milk to preterm infants tends to occur at a lower rate than that recorded among term infants. We aimed to investigate the facilitators of and barriers to breastfeeding during hospital stay according to the experiences of mothers that gave birth to premature infants requiring admission to neonatal intensive care unit. Methods A cross-sectional questionnaire survey was conducted. Mothers who had delivered a newborn with a gestational age ≤33 weeks requiring intensive care, entered the study. Basic subjects’ characteristics and infant feeding practices were also recorded. Results A total of 64 mothers were enrolled, leading to a total of 81 infants. At discharge, any breastfeeding was recorded in 66% of infants, with 27% of those infants being exclusively breastfed. Any infant was exclusively fed directly at the breast. Most mothers experienced adequate support during their infant’s hospitalization and reported satisfaction with breastfeeding. Almost all mothers felt that feeding their infant human milk was beneficial for the infant’s health. Thirty percent of the mothers reported that they had experienced some obstacles to breastfeeding. Specifically, infants born to mothers who experienced difficulties in pumping breast milk (OR = 4.6; CI 1.5–13.9) or in providing an adequate amount of milk to the infant (OR = 3.57; CI 1.1–11.5) were at higher risk of being fed with formula at discharge. Conclusions On the basis of the present results, health care professionals should target their efforts to optimize breastfeeding support for mothers of premature infants admitted to level III care, especially by improving breast milk production and endorsing direct breastfeeding.